DEVELOPMENT OF STOCK EXCHANGE AS TOOL ATTRACTION OF INVESTMENT OF REGION INDUSTRY - D. S. Tagaverdiyeva (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Development of stock market as instrument of attraction of investments into the industry Development of stock market as instrument of attraction of investments into the region industry In this article need of attraction of investments into the region for the purpose of overcoming of industrial recession and improvement of quality of life of the population, by means of development of stock market is considered. This problem arose in connection withbackwardness of the financial markets that, in turn, results in deficiency of investments in the region.Realization of a complex of actions of investment resources providing inflow to the region industry is necessary for the solution of a problem of attraction of investment resources.